Mindfulness-Based Learning and Interactive Storytelling in Multicultural Early Childhood Classrooms: Effects on Attention, Resilience, and Language - Krobo, Andrianus; Salhah; Muzdhalifah (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2026)
This study examined the contribution of Mindfulness-Based Learning integrated with Interactive Storytelling Media to children’s attention control, emotional resilience, and holistic language development in a multicultural early childhood classroom. Using a quasi-experimental non-equivalent pretest-posttest control group design, the study involved 60 children aged 5 to 6 years from the Laboratory Kindergarten of Universitas Negeri Malang. The experimental group received a structured intervention combining age-appropriate mindfulness activities with culturally responsive interactive storytelling, while the control group continued with conventional classroom learning. Data were collected through structured observation checklists and analyzed using independent-samples t-tests to compare post-intervention outcomes between groups. The results showed statistically significant differences across all developmental domains, with mean differences ranging from 0.63 to 0.89 and large effect sizes ranging from 0.92 to 1.20 (p < .001). Children in the experimental group demonstrated stronger gains in selective, sustained, shifting, and executive attention; emotional regulation, optimism, adaptability, and social support utilization; as well as linguistic development, cognitive-language integration, social-emotional communication, and cultural-contextual literacy. These findings suggest that mindfulness may strengthen attentional readiness and emotional regulation, while interactive storytelling provides meaningful opportunities for narrative engagement, expressive communication, and cultural understanding. The study contributes to global discussions on early childhood pedagogy by offering an integrated framework that connects self-regulation, socio-emotional learning, language development, and cultural responsiveness. Despite its promising findings, the study is limited by its short intervention period, restricted sample diversity, and reliance on observational measures, indicating the need for longitudinal and cross-cultural research with more objective assessment tools.